Pengaruh Persepsi Akuntansi, Pengetahuan Akuntansi, Skala Usaha dan Latar Belakang Pendidikan Terhadap Penggunaan Informasi Akuntansi - Rini, Lina Sekar; Witono, Banu (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to determine the effect of accounting perception, accounting knowledge, business scale and educational background on the use of accounting information. The research method in this study is classified as using quantitative research with a causal approach. The Data used in this study is a type of primary data. In this study the primary data was obtained by conducting field surveys and providing questionnaires. The questionnaire used a likert scale of 1-5. The population in this study is SMEs. Sample selection in this study using nonprobability sampling technique with convenience sampling. Based on the calculation, the sample of respondents in this study is 100 of the total number of MSME actors in Teras District, Boyolali regency. The results of research that has been done and the discussion that has been described can be concluded that the perception of accounting, accounting knowledge affect the use of accounting information, while the scale of business and background do not affect the use of accounting information.